Joining Past and Present Self-Stories:: The Narrative Complexity of Our Subjectivity - Sinha, Chandranshu (Narrative Works)

(untitled) (The University of New Brunswick, 2016)
This paper explores the links between the multilayered and multi-temporal complexities of the author’s past and present life stories, using autoethnography as a mode of inquiry to make sense of his subjective understanding of life. As such, it tries to assess the difference between experienced life history (his past experiences) and narrated life story (how he interprets these experiences from his present point of view) in order to show how one’s present self-description is determined by one’s past experiences. In the process, the paper explores how the author’s interest in narrative ideas has roots in the narrative of his own life.